2008
DOI: 10.3928/1081597x-20080301-04
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Experience With Mixing and Matching Refractive Array and Diffractive CeeOn Multifocal Intraocular Lenses

Abstract: <h4>PURPOSE</h4><p>To compare visual performance of the refractive Array SA40N and the diffractive CeeOn 811E multifocal intraocular lenses (IOLs) and to evaluate the potential benefits of combining both multifocal IOLs in the same patient. </p> <h4>METHODS</h4><p>Two groups of cataract patients were unilaterally implanted with either the CeeOn diffractive (n=10) or the Array refractive multifocal IOL (n=10). Another group was bilaterally implanted with one of each mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…Studies have shown how the concept of mixing and matching multifocal IOLs allows a wide range of vision at different distances with a high level of patient satisfaction. 15,17,18 However, the main shortcoming of refractive multifocal IOLs seems to be the higher rate of photic phenomena compared to the diffractive multifocal IOLs. 19 This drawback can penalize the mix and match technique in terms of quality of vision and patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown how the concept of mixing and matching multifocal IOLs allows a wide range of vision at different distances with a high level of patient satisfaction. 15,17,18 However, the main shortcoming of refractive multifocal IOLs seems to be the higher rate of photic phenomena compared to the diffractive multifocal IOLs. 19 This drawback can penalize the mix and match technique in terms of quality of vision and patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned longitudinal study found that 9.8% of an elderly population sample (n Z 6199) had only one IOL at the 2002 time pointdseveral years before AcrySof ReSTOR IOLs were available. Several studies [23][24][25][26] are available to guide the surgeon in mixing or matching multifocal technologies; however, many patients present with 1 monofocal IOL and 1 phakic cataractous eye. This study shows that a monofocal-multifocal IOL combination can produce good near UCVA (0.09 logMAR), better than might be expected by matching IOLs to produce bilateral monofocal IOLs, which yielded 0.41 logMAR in 1 study.…”
Section: Discussionmentioning
confidence: 98%
“…). Previous studies revealed that patients who underwent combined implantation of refractive and diffractive types of MIOLs had better near or intermediate visual acuity (VA) than patients who underwent bilateral implantation of monofocal IOLs or unilateral MIOL implantation (Gunec & Celik ; Chen et al. ; Yoon et al.…”
Section: Introductionmentioning
confidence: 99%